2020
DOI: 10.3390/biomedicines8030057
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Role of Apurinic/Apyrimidinic Endonuclease1/Redox Factor-1 as a Therapeutic Target for Vascular Inflammation and as a Serologic Biomarker

Abstract: Endothelial dysfunction promotes vascular inflammation by inducing the production of reactive oxygen species and adhesion molecules. Vascular inflammation plays a key role in the pathogenesis of vascular diseases and atherosclerotic disorders. However, whether there is an endogenous system that can participate in circulating immune surveillance or managing a balance in homeostasis is unclear. Apurinic/apyrimidinic endonuclease 1/redox factor-1 (henceforth referred to as APE1/Ref-1) is a multifunctional protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Increasing evidence indicates that APE1/Ref-1 expression is upregulated in several types of cancer, and in cardiovascular and inflammatory disorders [13]. APE1/Ref-1 is highly expressed in hypertensive rats [36] and in human atherosclerotic plaques [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence indicates that APE1/Ref-1 expression is upregulated in several types of cancer, and in cardiovascular and inflammatory disorders [13]. APE1/Ref-1 is highly expressed in hypertensive rats [36] and in human atherosclerotic plaques [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to uncover the mechanisms behind APE1/Ref-1 secretion. APE/Ref-1 can be secreted by using non-classical secretion pathways because of the absence of a leading peptide sequence [13]. The secretion of APE1/Ref-1 is mediated by ATP-binding cassette A1 (ABCA1) transporter or vesicular formation [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APE1/Ref-1 is a multifunctional protein that can be secreted from cells. In addition to its anti-inflammatory activity and modulation of redox status, APE1/Ref-1 is part of the DNA base repair pathway, affects several types of transcriptional factors, and thereby is essential for genomic stability [ 85 ]. The results showed that the levels of APE/Ref-1 mRNA increased significantly in the hippocampus of rats that were challenged with kainic acid and treated with raloxifene, compared to kainic acid challenged rats that were not treated with kainic acid.…”
Section: Intracellular Mechanisms (Nongenomic and Genomic) Modulatmentioning
confidence: 99%
“…In this case, APE1's role seems to be interesting to examine. Recently, a study characterized AP endnonuclease as a serological marker for vascular inflammation [122]. Moreover, Jin and co-workers observed that high concentrations of AP endonuclease strongly correlated with myocardial injury.…”
Section: Apurinic/apyrimidinic Endonuclease 1 In Monocyte Cells As a mentioning
confidence: 99%